2020
DOI: 10.3389/fped.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of Umbilical-Cord-Blood Procalcitonin-Based Algorithm on Antibiotics Exposure in Neonates With Suspected Early-Onset Sepsis

Abstract: Context: The incidence of early-onset neonatal infection has greatly decreased, but a new diagnostic approach is needed to avoid overdiagnosis and overtreatment. The aim of this study was to assess the potential impact of an algorithm incorporating umbilical-cord-blood procalcitonin (PCT) level on neonatal antibiotics prescription rate as compared with current practice. Material and methods: We conducted a prospective study in three maternity wards in France. All term and preterm neonates with the usual risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…Serum procalcitonin levels (PCT) in Group 1 subjects in relation to sepsis screen and blood culture in Olivia Oria de et al reported that in 'no sepsis' neonates' serum PCT was positive in 4.77% while 100% probable sepsis & proven sepsis neonates were PCT positive [18]. Similar results noted in Noemie Huetz et al study [19].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Serum procalcitonin levels (PCT) in Group 1 subjects in relation to sepsis screen and blood culture in Olivia Oria de et al reported that in 'no sepsis' neonates' serum PCT was positive in 4.77% while 100% probable sepsis & proven sepsis neonates were PCT positive [18]. Similar results noted in Noemie Huetz et al study [19].…”
Section: Discussionsupporting
confidence: 53%
“…The higher value of PCT positive newborns in positive PSS subjects in our study is most probably due to high number of preterm and low birth weight. Olivia Oria de et al study reported that serum PCT levels were negative in 120 (88.23%) & positive in 16 (11.77%) subjects, out of 136 subjects [18] Relationship in Serum procalcitonin levels (PCT) and sepsis screen reported by Noemie Huetz et al as 57 subjects had serum PCT levels ≥0.6 ng/ml with positive sepsis screen in 16(28.07%) and negative in 41(71.93%) & serum PCT levels < 0.6 ng/ml in 3023 subjects, with positive sepsis screen in 23(0.76%) and negative in 3000 (99.24 %), other studies also depicted similar results [7,19,25,26,29]. Variations in the results of studies by different workers are due to respective cut-off values.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Umbilical cord sampling precedes this physiological peak and has shown to be a reliable method to aid decision making in an early stage (21). Recently, it has been shown that an umbilical cord PCTbased algorithm has the potential to decrease the number of preterm newborns that receive antibiotic therapy (22). Until now, no study has focused on the potential difference between venous umbilical cord blood, which originates from the mother or placenta, and arterial cord blood, originating from the newborn.…”
Section: Introductionmentioning
confidence: 99%